Dietary Fiber Supplementation in Replacement Gilts Improves the Reproductive Performance From the Second to Fifth Parities - Zhuo, Yong; Hua, Lun; Che, Lianqiang; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; Wang, Jianping; Li, Jian; Feng, Bin; Wu, De (Frontiers in Veterinary Science, 2022)
This study examined the effects of soluble fiber (SF) supplementation (0.8%), containing 17.4% rhamnose, 4.1% fucose, 11.1% arabinose, 30.6% xylose, and 16.4% galactose during the prepubescent phase on the subsequent performance from the second to fifth parities. After the first parity, 56 and 55 post-weaning sows in the control (CON) and SF groups had their reproductive performance monitored in succeeding parities. Circulating concentrations of anti-mullerian hormone (AMH) were greater in the SF group than in the CON group at 205 d of age and the first post-weaning day (p < 0.05). The SF treatment at the prepubescent phase resulted in an enhanced reproductive performance from parities three to five. In Parity three, the SF sows had 1.32 total born (p = 0.044), 1.43 born alive (p = 0.023) and 1.40 born effective, which was significantly more than in the CON group (p = 0.022). In Parity four, the SF sows had 1.1 total born (p = 0.058), 1.28 born alive (p = 0.019), and 1.06 born effective, significantly more than in the CON group (p = 0.049). In Parity five, the SF gilts had 1.43 total born (p = 0.075), 1.53 born alive (p = 0.067) and 1.65 born effective, significantly more than in the CON group (p = 0.020). No effects were observed for the removal of sows and backfat thickness at the mating in each parity between groups (p > 0.05). Collectively, gilts that received an extra 0.8% SF during the prepubescent phase increased their subsequent litter size as breeding sows. These results showed that nutritional decisions at the replacement phase could influence lifetime fertility.